Uji Kualitas Air Minum Isi Ulang Dengan Parameter Mikrobiologi Di Kelurahan Berngam Kota Binjai - Eka Setiawan Siregar; Abdul Karim; Rahmiati rahmiati (Universitas Medan Area, 2019)
Refilled drinking water is one of the alternatives for the need of drinking water. Drinking water is safe for health when it meets physical, microbiological, chemical, radioactive requirements. The purpose of this study was to determine the quality of refilled drinking water with microbiological parameters (coliform dan E. coli) in the Berngam Village of Binjai city in 2018. The method of this research was descriptive research with laboratory tests. The research sample is the entire population of refill drinking water depots located in the Berngam Village of Binjai City in 2018. The results of the study showed that seven samples of refilled drinking water in the Berngam Urban Village had fulfilled the physical and chemical quality in according to them Permenkes R.I. No.492/Menkes/Per/IV/2010. While the quality of microbiology has not been fulfilled because it contains coliform and E. coli bacteria. It is recommended that the Puskesmas management provide counseling and monitoring for the owners of refilled drinking water depots in order to realize qualified drinking water for people.